The Question of Diasporic Trauma in Kamila Shamsie’s Home Fire - Abdulkadir Ünal (Ideas: Journal of English Literary Studies)
The exploration of second-generation diasporic trauma in Kamila Shamsie’s seventh novel, Home Fire (2017), depicts a struggle to reconcile with the past of the characters with both Pakistani and British nationality. Shamsie consolidates her fiction about the dilemma and struggle of the diasporic society members, Isma, Aneeka and Parvaiz, throughout the novel. The recurring motif of the novel is the diasporic identity which signals the dilemma of the characters in terms of adopting British or Pakistani moral norms and identities. Shamsie justifies the diasporic trauma as a revelation of the present and past diasporic belongings of Knickers Pasha and Pervy Pasha in the novel as a characteristic of vile and modern migrant tragedies. In this study, the notion of diasporic trauma will be studied in the novel, Home Fire, with the fragmented narrative voices of the Pasha family members as one of the means of representation of trauma in literature.